Identification of anticoagulation quality in patients using warfarin and associated factors: DOI: 10.15343/0104-7809.202145003009 - de Faria Martins Braga, Lucas (2021)
Warfarin is an oral anticoagulant widely used in the prevention of thromboembolic events and is made available by the Brazilian Unified Health System. However, maintaining the quality of oral anticoagulation is a challenge in clinical practice, other than the identification of factors that interfere in this important process for the clinical and scientific context. This was a cross-sectional study, conducted at a university hospital in Minas Gerais, with the objective of identifying the quality of oral anticoagulation in patients using warfarin and associated factors. The quality of anticoagulation was assessed using the time in therapeutic range (TTR), which allows the identification of the proportion of time in which the patient presented international normalized ratio (INR) values within the desired therapeutic range. TTR values were associated with clinical and demographic characteristics using univariate and multivariate logistic regression. The mean TTR was 61.8% (SD + 1.00), with 204 (46.3%) patients demonstrating inadequate anticoagulation control. The variables gender (OD: 1.82; P: 0.005; CI: 1.204335-2.761345), use of warfarin other than prescribed (OD: 2.81; P <0.005; CI: 1.700- 4.632352) and bleeding occurrence (OD: 1.70; P <0.005; CI: 1.013157-4.632352) were predictors of inadequate TTR. Indications for use, thromboembolism and valvulopathy were predictors of adequate TTR. The findings contribute to a better understanding of the profile of patients with inadequate control of oral anticoagulation and the establishment of strategies that promote anticoagulation quality.